Legal Verses About Women's Dignity and Actualization of Gender Equality in the Family - Nawawi, M Anwar; Zainuri, Muhammad; AB, Balik Jaya; Ibrahim, Rosita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This article is about legal verses related to the noble status of women. So far, some people still think that the status of women is not as special as that of men. Such an assumption has a serious impact on gender inequality in the household, women are often positioned as officers who play a role in